Potencial antibacteriano de fitoquímicos isolados ou em combinação com antimicrobianos frente à bactérias patogênicas para peixes - Bandeira Junior, Guerino (2018)
Brazilian aquaculture production is intensifying, leading to an increase of bacterioses, causing economic losses in fish farms. This increases the use of antimicrobials, often indiscriminately, causing bacterial resistance to them. The use of increasing concentrations of antimicrobials also leads to residues deposition in the aquatic environment and fish meat, generating a public health problem. Worsening the situation, only the antimicrobials florfenicol and oxytetracycline are legalized for use in the continental aquaculture, being necessary the discovery of new effective and safe active principles. Essential oils and their isolated substances (phytochemicals) have shown antimicrobial effect, representing potential drug candidates. Aeromonas hydrophila, A. veronii, Citrobacter freundii, and Raoultella ornithinolytica are bacteria species found in silver catfish (Rhamdia quelen) naturally infected and that presented high mortality. In order to minimize the use of antimicrobials in fish culture, this study aims to evaluate the in vitro antimicrobial activity of the phytochemicals carvacrol, citral, eugenol, linalool, and thymol isolated and in combination with conventional antimicrobials (florfenicol and oxytetracycline), as well as to evaluate the inhibition potential of hemolysis and biofilm formation of fish pathogenic bacteria. The results demonstrated that when analyzed isolated, carvacrol, thymol, and eugenol presented better activity. Most of the combinations showed additivity, and three of them were synergistic: linalool with florfenicol or oxytetracycline against A. hydrophila, and citral with oxytetracycline against C. freundii. Phytochemicals showed no antagonistic interaction with conventional antimicrobials, allowing their combined use, which may contribute to the reduction of the conventional drugs concentrations, reducing their residues in the aquatic environment. The five phytochemicals demonstrated ability to inhibit the hemolysis of a β-hemolytic A. hydrophila strain when used at concentrations lower than those required to inhibit bacterial growth. The phytochemicals also demonstrated potential to inhibit the biofilm formation of the bacteria, and this inhibition is possibly greater than that caused by conventional antimicrobials.